CULTURE PATTERNS OF BTS FANS IN THE DIGITAL ERA ON THE @INDOMY TWITTER - Desmiati, Desmiati (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2023)
This article aims to examine the ARMY fandom and see how the new fan culture in the digital era is implemented on the social media Twitter account @INDOMY. This research used method of etnography virtual by Christine Hine (2015). There are two data collection techniques used, namely exploring field sites on the Twitter account @INDOMY and literature review of previous research as additional data to complete research information needs. The results of the study show that fan culture can be seen from four things in the context of the field of fandom on the internet: 1) communication, showing that fans use virtual identities in communicating and producing fan speaking and fan jokes. 2) creativity, fans generate various forms of creative production i.e., memes, fan edits, fan covers and fan fiction, 3) knowledge, in this area the fan base is responsible for providing information to fandom members, and 4) civic power, fans success through fan projects consisting of fan streaming, fan voting, birthday projects and charity activities through donations made by fans. Keywords: Fandom; Fans Culture; Twitter; ARMY.